“A Whole New Take on Indigenous”: Margaret Atwood’s Oryx and Crake as Wild Animal Story - Frew, Lee (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
Margaret Atwood’s MaddAddam trilogy has met with popular acclaim and generated considerable scholarly interest since the 2003 publication of its first volume, Oryx and Crake. The implicit critique of Western capitalism presented in Atwood’s dystopian vision of a post-democratic, post-national, and post-human future seems to offer a wide appeal, particularly at a time of sustained environmental crisis. Instead of evaluating the merits of Atwood’s critique, however, this paper examines the ways in which the speculative future of Oryx and Crake and the warnings it contains are delimited by a problematic Second World paradigm. More specifically, the novel can be read in terms of the wild animal story, a genre first established in late-nineteenth-century Canada that Atwood herself was instrumental in defining as such in her controversial 1972 study Survival: A Thematic Guide to Canadian Literature. In keeping with the conventions of the wild animal story, boundary crossings in Atwood’s novel engage in indigenizing fantasy. Despite its powerful warning of imminent disaster, Oryx and Crake nevertheless obscures ongoing colonializing acts by privileging a settler subject-position conceived as endangered by the forces of modernity